2001
DOI: 10.1095/biolreprod65.4.1252
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Rat Leydig Cell Steroidogenic Function by Di(2-Ethylhexyl)Phthalate1

Abstract: Exposure of rodents to phthalates is associated with developmental and reproductive anomalies, and there is concern that these compounds may be causing adverse effects on human reproductive health. Testosterone (T), secreted almost exclusively by Leydig cells in the testis, is the primary steroid hormone that maintains male fertility. Leydig cell T biosynthesis is regulated by the pituitary gonadotropin LH. Herein, experiments were conducted to investigate the ability of di(2-ethylhexyl)phthalate (DEHP) to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
182
3
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(208 citation statements)
references
References 31 publications
18
182
3
5
Order By: Relevance
“…Testicular steroids were extracted from the testes of control and DEHP-exposed pups (n ϭ 10 control; n ϭ 12 DEHP), as described. T concentrations were measured by a tritium-based RIA validated for use with rat antiserum, as described (8,9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular steroids were extracted from the testes of control and DEHP-exposed pups (n ϭ 10 control; n ϭ 12 DEHP), as described. T concentrations were measured by a tritium-based RIA validated for use with rat antiserum, as described (8,9).…”
Section: Methodsmentioning
confidence: 99%
“…Controversy exists over whether DEHP, at the levels found in the environment, is harmful to humans, because most studies have been conducted in rodents administered high doses. In previous studies, we showed that the administration of low-dose (10 mg/kg body weight) DEHP for 28 days during pubertal development caused elevations in testosterone (T) (8,9). This was in contrast to doses Ͼ750 mg/kg, which significantly reduced serum and testicular T (10).…”
mentioning
confidence: 96%
“…Humans and wildlife populations are continuously exposed to EDCs, which are constantly discharged into the atmosphere and natural aquatic bodies (Kavlock et al, 2002). The PEs' mode of action, is not well understood, and may likely be dependent on developmental timing and dosing regimes (Akingbemi et al, 2001). Studies on rodents have identified Leydig cells as one of the main targets of phthalate-ester induced toxicity (Akingbemi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hingegen trat bei präpubertären Ratten eine erhöhte testikuläre Testosteronproduktion ab 10 mg/kg KG und Tag nach 14-tägiger Exposition vom 35 bis 48. Postnataltag über das Futter (Akingbemi et al 2001) und ab 5 mg/m 3 nach vier-und achtwöchiger inhalativer Exposition ab dem 28. Postnataltag (Kurahashi et al 2005) auf.…”
Section: Antiandrogene Wirkungunclassified
“…Postnataltag (Kurahashi et al 2005) auf. Die Steroidgenese in den Leydigzellen wird beeinflusst durch die Entwicklungsstufe während der Exposition und dürfte durch die Modulation der Aktivität von an der Steroidgenese beteiligten Enzyme und der Serum-LH (Luteinisierendes Hormon)-Konzentrationen erfolgen (Akingbemi et al 2001). Im Folgenden werden nur Untersuchungen an den Hoden männlicher Feten von während der Gestation behandelten Muttertieren sowie In-vitro-Experimente zur Klärung des Wirkungsmechanismus berücksichtigt.…”
Section: Antiandrogene Wirkungunclassified